PENGARUH PEMBELAJARAN TEMATIK TERPADU SHARED TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Ade Islamiati; Yanti Fitria; Yeni Erita (STKIP Subang, 2023)
This research is motivated by the lack of motivation of students to attend and study at school so that it will have a negative impact on the learning outcomes of these students. The purpose of this study was to analyze how the effect of the Shared Integrated learning model on increasing the learning motivation of students, especially for students who are at the elementary school level. This type of research is qualitative research where researchers collect various information from reviewing journals related to the problem and conducting literature studies. Literature study here researchers do by collecting related data. In its implementation in the learning process, this integrated learning model is generally used by educators at Elementary Schools because this integrated learning model is appointed according to what is needed for the development of students. What is expected in this study is to be able to increase student learning motivation so that it will also have an impact on the learning outcomes achieved by these students.